The design and evaluation of the P₀.₁ method of assessing ventilatory drive - Gajjar, Narendrakumar Chhotalal (Division of Biomedical Engineering, 2019)
Hypercapnia and/or hypoxia normally cause hyperventilation, The sensitivity to hypercapnia and hypoxia and the resultant hyperventilation is reduced in a patient suffering from damped respiratory centre activity. The P 0.1 method is a modification of the rebreathing technique where a patient rebreathes from a bag prefilled with a mixture of gases of known concentrations. This modification is not sensitive to airflow obstruction as is the case with the ventilatory response of the rebreathing technique. The P 0.1 method has been described by several authors during the past 8 years. There is however the need to standardise the technique. This thesis is an attempt to meet this need. The P 0.1 method involves the occlusion of the inspiratory airway for a set time after the onset of inspiration of a particular breathing cycle. The pressure (P 0.1) at this time, generated by the isometric contraction of the respiratory muscles, is recorded together with the end tidal P C02 . The valve is occluded approximately 20 times during a rebreathing trial lasting for 4 minutes. The plot of P 0.1 versus P C02 is linear and its slope gives an indication of respiratory centre activity. A low slope indicates damped respiratory centre activity. The control electronics was designed using digital logic. The occlusion valve is closed passively during the expiratory phase and then actively held for a preselected time, most frequently for 1OOms, after the onset of inspiration, during the next breathing cycle. The active occlusion period is preselectable between 50ms and 300ms. The inspiratory pressure is recorded at this time, or 10 or 20ms prior to the opening of the valve, by a sample and hold circuit. The occlusion valve can be triggered manually via a push button switch on the front panel, or periodically for preselectable periods every 5 to 30 seconds or pseudo-randomly. Ventilatory phase, pressure preset and autotrigger mode indicators are included as operator aids. In a limited number of clinical trials the equipment worked satisfactorily. During a hypercapnic study the CO2 concentration in the bag progressively increases with a resultant increase in ventilation. The hypercapnic trials carried out yielded encouraging results. The method is simple, rapid and easily reproducible. The regression line plots obtained are linear with correlation coefficients better than those presented in the literature. The sensitivity of the ventilatory drive defined as the slope of the P 0.1 versus P C02 regression line for a group of 10 healthy adult males tested was 0.79 ± 0.47 cmH 2 o/mmHg. The device is in clinical use in the Respiratory Clinic at Groote Schuur Hospital. Further work needs to be done to investigate the full meaning of the results obtained and to what extent it can be used as a noninvasive diagnostic and screening technique for respiratory disorders. The P 0.1 method will help the clinician to assess non-invasively the degree of impairment of respiratory centre output in patients suspected of having a damped respiratory centre and who may also suffer pulmonary mechanical defects because the technique is independent of airflow.